Collective Flourishing: A Response to Anantanand Rambachan - Newman, Kate (Journal of ecumenical studies, 2018)
The article focuses on Anantanand Rambachan, a Hindu theologian speaking in a Christian ceremony, and words anew as pertaining not only to marriage but also to relationships between people across religious traditions. It mentions Hindu theologian who offers his tradition's wisdom to a Christian couple enfleshes a possibility that we cannot help but hear in Rambachan's words. It also mentions commitment to multiple understandings of divinity and collective interreligious friendship.